Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Help me please translations hw

Help Me Please Translations Hw class=

Sagot :

The locations of the vertices are shown below:

  1. (- 5, 4), (- 4, 4), (- 5, 2)
  2. (- 4, 1), (- 1, 2), (0, - 1), (- 2, - 5)
  3. (2, 5), (3, 4), (1, 2)
  4. (3, - 5), (- 2, - 3), (0, - 1)

What are the coordinates of the images resulting from a translation?

Herein we find four representations of polygons on Cartesian plane and we must determine the coordinates of the images generated by translation, a kind of rigid transformations. Translation is described by the following operation:

P'(x, y) = P(x, y) + T(x, y)

Where:

  • P(x, y) - Original point
  • P'(x, y) - Resulting point
  • T(x, y) - Translation vector

Case 1 (K(x, y) = (3, - 3), X(x, y) = (4, - 3), R(x, y) = (3, - 5), T(x, y) = (- 8, 7))

K'(x, y) = (3, - 3) + (- 8, 7) = (- 5, 4)

X'(x, y) = (4, - 3) + (- 8, 7) = (- 4, 4)

R'(x, y) = (3, - 5) + (- 8, 7) = (- 5, 2)

Case 2 (E(x, y) = (0, 2), X(x, y) = (3, 3), V(x, y) = (4, 0), Z(x, y) = (2, - 4), T(x, y) = (- 4, - 1))

E'(x, y) = (0, 2) + (- 4, - 1) = (- 4, 1)

X'(x, y) = (3, 3) + (- 4, - 1) = (- 1, 2)

V'(x, y) = (4, 0) + (- 4, - 1) = (0, - 1)

Z'(x, y) = (2, - 4) + (- 4, - 1) = (- 2, - 5)

Case 3 (G(x, y) = (- 4, 5), J(x, y) = (- 3, 4), U(x, y) = (- 5, 2), T(x, y) = (6, 0))

G'(x, y) = (- 4, 5) + (6, 0) = (2, 5)

J'(x, y) = (- 3, 4) + (6, 0) = (3, 4)

U'(x, y) = (- 5, 2) + (6, 0) = (1, 2)

Case 4 (V(x, y) = (0, 0), Y(x, y) = (- 5, 2), F(x, y) = (- 3, 4), T(x, y) = (3, - 5))

V'(x, y) = (0, 0) + (3, - 5) = (3, - 5)

Y'(x, y) = (- 5, 2) + (3, - 5) = (- 2, - 3)

F'(x, y) = (- 3, 4) + (3, - 5) = (0, - 1)

To learn more on rigid transformations: https://brainly.com/question/28004150

#SPJ1

Answer:

See attachments.

Step-by-step explanation:

A translation is a type of transformation that moves a figure left, right, up or down.  Every point on the original figure is translated (moved) by the same distance in the same direction.

  • If a figure is to be moved left, subtract the number of units it is to be moved from the x-values.
  • If a figure is to be moved right, add the number of units it is to be moved to the x-values.
  • If a figure is to be moved up, add the number of units it is to be moved to the y-values.
  • If a figure is to be moved down, subtract the number of units it is to be moved from the y-values.

Question 1

Coordinates of the given pre-image:

  • K = (3, -3)
  • R = (3, -5)
  • X = (4, -3)

Given mapping rule:

[tex](x, y) \rightarrow (x-8, y+7)[/tex]

This tells us to subtract 8 from the x-values and add 7 to the y-values.

[tex]\sf \implies K(3,-3) \rightarrow K'(3-8, -3+7)=K'(-5,4)[/tex]

[tex]\sf \implies R(3,-5) \rightarrow R'(3-8, -5+7)=R'(-5,2)[/tex]

[tex]\sf \implies X(4,-3) \rightarrow X'(4-8, -3+7)=X'(-4,4)[/tex]

Question 2

Coordinates of the given pre-image:

  • E = (0, 1)
  • X = (3, 3)
  • V = (4, 0)
  • Z = (2, -4)

Given mapping rule:

[tex](x, y) \rightarrow (x-4, y-1)[/tex]

This tells us to subtract 4 from the x-values and subtract 1 from the y-values.

[tex]\sf \implies E(0,1) \rightarrow E'(0-4, 1-1)=E'(-4,0)[/tex]

[tex]\sf \implies X(3,3) \rightarrow X'(3-4, 3-1)=X'(-1,2)[/tex]

[tex]\sf \implies V(4,0) \rightarrow V'(4-4, 0-1)=V'(0,-1)[/tex]

[tex]\sf \implies Z(2,-4) \rightarrow Z'(2-4, -4-1)=Z'(-2,-5)[/tex]

Question 3

Coordinates of the given pre-image:

  • G = (-4, 5)
  • J = (-3, 4)
  • U = (-5, 2)

Given mapping rule:

[tex](x, y) \rightarrow (x+6, y)[/tex]

This tells us to add 6 to the x-values and the y-values remain unchanged.

[tex]\sf \implies G(-4,5) \rightarrow G'(-4+6, 5)=G'(2,5)[/tex]

[tex]\sf \implies J(-3,4) \rightarrow J'(-3+6, 4)=J'(3,4)[/tex]

[tex]\sf \implies U(-5,2) \rightarrow U'(-5+6, 2)=U'(1,2)[/tex]

Question 4

Coordinates of the given pre-image:

  • F = (-3, 4)
  • V = (0, 0)
  • Y = (-5, 2)

Given mapping rule:

[tex](x, y) \rightarrow (x+3, y-5)[/tex]

This tells us to add 3 to the x-values and subtract 5 from the y-values.

[tex]\sf \implies F(-3,4) \rightarrow F'( -3+3, 4-5)=F'(0,-1)[/tex]

[tex]\sf \implies V(0,0) \rightarrow V'( 0+3, 0-5)=V'(3,-5)[/tex]

[tex]\sf \implies Y(-5,2) \rightarrow Y'( -5+3, 2-5)=Y'(-2,-3)[/tex]

Learn more about transformations here:

https://brainly.com/question/28354239

View image semsee45
View image semsee45
View image semsee45
View image semsee45